Exploring Speaking-Anxiety Triggers in Polytechnic ESP Course: An Inductive Thematic Analysis - Romadloni, Annisa; Sari, Laura; Wanti, Linda Perdana (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study investigates the specific moments and conditions that trigger speaking anxiety among engineering undergraduates in an English for Specific Purposes (ESP) course at a Politeknik Negeri Cilacap. Drawing on open‐ended responses from 101 students, the primary goal was to uncover the classroom scenarios—beyond general anxiety scales—that most disrupt learners’ oral performance. Narrative data were repeatedly reviewed following Braun and Clarke’s inductive thematic analysis procedures; provisional codes for anxiety‐provoking incidents (e.g., more comfortable in a small group, fear of being laughed at, nervous when unprepared) were generated and organized into coherent themes. It is anticipated that speaking anxiety will be found at a moderate level, with the greatest distress being associated with lexical retrieval under time pressure and unprepared, impromptu speaking tasks. Secondary triggers are expected to include concerns about grammatical accuracy and pronunciation, while social factors—such as instructor scrutiny or mixed‐gender audiences—will likely play a smaller role. These predicted patterns underscore the dual burden of technical content mastery and language production in ESP contexts. By pinpointing discipline‐specific anxiety triggers, this work aims to inform targeted pedagogical interventions—like scaffolded vocabulary drills, brief planning aids, and supportive feedback practices—to help ESP instructors foster more confident, resilient speakers.